Development Of A Green Chemistry Module Based On Project-Based Learning - Anggi Ristiyana Puspita Sari; Ruli Meiliawati; Suandi Sidauruk; Agtri Wulandari; Fatchiyatun Ni'mah (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2024)
The Sustainable Development Goals (SDGs) present new challenges in global competition. This has been reflected in the Merdeka Curriculum, which incorporates green chemistry materials and project-based learning models. However, the lack of project-based learning module has become a significant obstacle in implementing this curriculum in schools. This research aims to determine the quality of the green chemsitry module that was developed. The product development follows the ADDIE model, though the research only covers the development stage. The initial product was reviewed by 6 experts to assess its quality. A Likert-scale questionnaire was used as the evaluation instrument, consisting of four components with a total of 33 statements. Meanwhile, the user response instrument consisted of 12 statements. The results showed that the project-based green chemistry module was deemed feasible for implementation in learning. This was evidenced by the ideal percentage from the product feasibility assessment by experts at 95.95%, which falls into the Very Good category. Furthermore, the small-scale trial results indicated an ideal percentage of 82.58% categorized as Good. This module supports the implementation of SDGs in reducing environmental pollution, as it includes several projects that students can apply in waste management.